Occupational disruption during a pandemic: Exploring the experiences of individuals living with chronic disease. Issue 3 (3rd July 2022) - Luck, Kerrie E.; Doucet, Shelley; Luke, Alison
ABSTRACT: The aim of this study was to explore the experiences of occupational disruption during a pandemic among individuals living with chronic disease, with particular attention to experiences related to managing disease(s) and routine healthcare. This qualitative descriptive study using virtual semi-structured interviews was conducted with 23 participants diagnosed with chronic disease(s) for at least 2 years, living in New Brunswick, Canada. Three overarching themes, and seven sub-themes emerged from the thematic analysis: 1) reactions (sub-themes: occupational loss and loneliness; fear and vulnerability); 2) adaptations (sub-themes: engaging in new or re-discovered occupations; prioritizing self-management; changing perspective); and 3) barriers (sub-themes: limited access to care; environmental challenges). Individuals living with chronic disease modified what they did to provide structure and purpose in response to restrictions imposed on their regular day-to-day occupations and the feelings this evoked. Notably, participants reported a heightened engagement in occupations focused on maintaining health and well-being; however, not all adaptations resulted in positive outcomes. Reactions such as fear and vulnerability influenced behavior and contributed to apprehension to seek out medical care. Changes in the environment also created barriers and challenged the participants' ability to adapt. This research offers the first glimpse inside this occupational paradigm, to not only enhance understanding of the impact of COVID-19 on individuals living with chronic disease, but also to strengthen knowledge of what is needed to improve communication, organization, and the provision of care for individuals living with chronic disease both during a pandemic and in everyday life.